THE EFFECTIVENESS OF USING VOCABULARY VIDEO TO IMPROVE THE VOCABULARY MASTERY OF THE FOUR GRADE STUDENTS OF SDN SUGIWARAS IN ACADEMIC YEAR 2014 - PRATAMA, TRI ANDI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key words: the vocabulary mastery, the vocabulary video, the students, SDN 1Sugiwaras. The purpose of this study is to find out the effectiveness of vocabulary video in teaching English vocabulary at fourth grade at SDN Sugiwaras Candi Sidoarjo. This technique can improve and increase student’s ability to learn the target language and make them enjoy teaching learning process. It supposes to motivate students to learn English actively by using vocabulary video. Students also are encouraged to get long memorizing of the words and their meaning.The method that is used in this study is the quasi experimental method by using t-test, to find out the significant difference between recent technique and vocabulary video technique through the score pre-test and post-test.The result of analysis in the study showed that teaching vocabulary by using vocabulary video is success. Using vocabulary video made process learning effective and made students motivated, so it can be used as an alternative method in teaching vocabulary based on the result of gained post-test students’ achievement at the Fourth Grade of SDN Sugiwaras Candi Sidoarjo year of 2014.The school should give wider opportunity for the teacher to use “Vocabulary Video” as medium on teaching English vocabulary. It is important because this study found significant difference between the mastery of English vocabulary of the fourth grade students of SDN Sugiwaras, Candi Sidoarjo in academic year of 2014 before and after being taught by using vocabulary video.